Exploring the Mediating Effect of Financial Literacy on the Relationship between Financial Attitude, Financial Knowledge, and Financial Management Behavior: Evidence from Millennials in Malang City, Indonesia - Diana Alvia Safitri; Miftahul Huda (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of financial attitude and financial knowledge on the financial management behavior of the millennial generation mediated by financial literacy. The study was conducted among 100 millennial respondents in Malang City using a quantitative approach and Path analysis via SPSS software. The results indicate that financial attitude has a significant direct effect on financial management behavior and financial literacy; however, it does not exhibit a significant indirect effect through the mediation of financial literacy. In contrast, financial knowledge exerts a significant direct influence on financial management behavior and financial literacy and demonstrates a significant indirect effect via financial literacy. This suggests that the financial knowledge millennials possess more effectively shapes financial management behavior when supported by a high level of financial literacy. These findings underscore the critical role of financial literacy in enhancing the impact of financial knowledge on millennials' financial decision-making. Consequently, financial education initiatives should prioritize improving financial literacy to maximize the benefits derived from financial knowledge.